Nihajoča asimetrija rogovja srnjakov (Capreolus capreolus L.) kot kazalec onesnaženosti okolja in pripomoček za upravljanje s populacijami - Pokorny, Boštjan (Zbornik gozdarstva in lesarstva, 2004)
Fluctuating asymmetry (FA), which represents non-directional differences between the left and the right side, was measured for nine bilateral traits inthe antlers of 282 roe deer, shot in the period 1961 - 2002 in the Šalek Valley. Our findings were as follows: (a) Five traits (antler length, length of both front and back tine, total beam length, and pedicle diameter) are suitable for FA analyses, since they fulfil the necessary statistical criteria. (b) A significant positive correlation between size and asymmetry exists for all traits; therefore, roe deer antler asymmetry does not reflect the quality of an individual. (c) Yearlings, whose antler asymmetry is not a suitable bioindicator of environmental pollution due to an incomplete ontogenetic development, have significantly higher FA in comparison with adults. (d) In the Šalek Valley, roe deer antler FA has been decreasing since 1980; after the construction of the desulphurization device in the Šoštanj Thermal Power Plant it is significantly lower in comparison with the period before construction. (e) On the generation level, there is a significant positive correlation between mean Pb levels in antlers and their mean FA, which identifies environmental pollution as one of the main stressors causing deviation from bilateral symmetry of deer antlers.
Keywords: okolje; onesnaženost; rogovje; simetrija; srnjad; Šaleška dolina